2009
DOI: 10.1007/s00198-009-0851-z
|View full text |Cite
|
Sign up to set email alerts
|

Sex steroids during bone growth: a comparative study between mouse models for hypogonadal and senile osteoporosis

Abstract: Bone fragility in both models resulted from deficient bone build-up during early puberty. DHT and E2 improved bone mass acquisition in orchidectomized animals, suggesting a role for AR and ER in male skeletal development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
3
0
2
Order By: Relevance
“…According to previous studies, the bone mass of the laboratory mice with a life-span of 2-3years, reaches its maximum between 4 to 8 months, after which the bone mass decreases with time [19,20]. We purchased 2, 5, 7 and 10 months old C57BL/6 female mice (n = 6) and measured their bone mineral density (BMD) by micro computed tomography (µCT).…”
Section: Mouse Models Of Senile Osteoporosismentioning
confidence: 99%
“…According to previous studies, the bone mass of the laboratory mice with a life-span of 2-3years, reaches its maximum between 4 to 8 months, after which the bone mass decreases with time [19,20]. We purchased 2, 5, 7 and 10 months old C57BL/6 female mice (n = 6) and measured their bone mineral density (BMD) by micro computed tomography (µCT).…”
Section: Mouse Models Of Senile Osteoporosismentioning
confidence: 99%
“…Although estrogen is considered by some to exert primarily inhibitory actions on periosteal expansion, there is recent evidence from animals models that many of the actions of estrogen on periosteum may be to stimulate expansion through ERα, but in a dosage sensitive manner, and potentially, in collaboration with androgen actions [76,76,97,113,114] on periosteally located AR [114]. However, recent studies have found that estrogen does not have an independent effect on periosteal expansion and that the action of estrogen and bone loading on bone structure are independent and additive [115].…”
Section: Bone Mineral Density and Architectural Integrity In Humanmentioning
confidence: 99%
“…Specifically, wrist breadth at time of presentation of the hERKO man was greater than normal at 7.2 cm (normal adult males: 6.0 ± 0.5 [mean ± SD]; normal adult females: 5.3 ± 0.3 cm) and the width of the distal femurs were both estimated to be 113 mm (normal adult male 90 ± 7 mm). The skeletal “frame size” as measured at the wrist and knee is distinctly different from the ectomorphic appearing skeleton of longstanding hypogonadism [116] and this phenotype may be due to important actions of androgen in these individuals [79,97,113]. The ArKO subjects have normal to slightly elevated androgen prior to intervention and this may serve to maintain and/or augment bone size.…”
Section: Bone Mineral Density and Architectural Integrity In Humanmentioning
confidence: 99%
“…Besonders die Effekte auf den Knochenstoffwechsel sind im Hinblick auf die Behandlung der Osteoporose interessant. Dass Androgene wie Testosteron und DHT auf den Knochen wirken, konnte unter anderem an männlichen orchiektomierten Nagern (Ophoff et al 2009, Vandenput et al 2002, Vanderschueren et al 1992) sowie an Männern aufgezeigt werden (Anderson et al 1997). In der männlichen Adoleszenz führen Androgene zu einer starken periostalen Apposition und folglich zu einer dickeren Kortikalis (Seeman 2001a, Seeman 2001b.…”
Section: öStrogenmangel Führt Zu Einemunclassified